Explaining Attitudes Toward U.S. Energy Extraction: Offshore Drilling, the Keystone XL Pipeline, and Hydraulic Fracturing. (14th August 2017) - Ceccoli, Stephen
Abstract : Objective: This research develops and tests several individual‐level explanations of citizen attitudes toward offshore drilling, the Keystone XL pipeline, and hydraulic fracturing. Methods: Using survey data from the Pew Research Center, logistic regression models analyze the effects of partisan and ideological considerations, presidential approval, affect for various levels of government, and a number of demographic considerations. Results: Findings indicate that partisan, ideological, and core value considerations are highly influential in shaping individual sentiment toward the energy policies. Further, evidence for the affect heuristic suggests important empirical divides are also found with respect to patterns of citizen orientation to President Obama, his energy policies, and to federal and local governments. Conclusion: These results are important in the context of previous assertions that energy policy and its regulatory character have changed over time and remain highly partisan and politically polarized. Additionally, citizen patterns of orientation, including measures of affect as encapsulated by the affect heuristic, also provide citizens with important shortcuts when developing attitudes toward the three policies.